Performance of Wheat as Alley Crop Grown with Morus alba Hedgerows Under Rainfed Conditions - Thakur, P.S.; Dutt, V. (Indian Journal of Agroforestry, 2020)
The impact of hedgerows of Morus alba, an important fuel and fodder agroforestry tree species of temperate region, during second and third year of establishment has been observed on the performance of wheat under rainfed conditions. Hedgerows of Morus alba with plant spacings of 1.5m (888 stems ha-1), 2m (666 stems ha-1) and 2.5 m (533 stems ha-1) caused considerable shade to the plots, especially at closer spacing and closer distance from the hedgerows. Growth, yield, root and physiological parameters were negatively influenced by the presence of hedgerows. Hedgerows in third year caused greater grain and biological yield reduction compared to second year of hedgerow establishment. Compared to control (without tree), plant height, spike number and leaf area index were reduced to greater extent in wheat under Morus hedgerow tree spacing of 1.5 m. The negative impact of hedgerows reduced with increasing distance up to 3 m from tree rows. Thousand grain weight, biological yield, grain yield and harvest index showed more reduction compared to control up to 1m distance from hedgerows. Production efficiency in wheat during second year (2002) and third year (2003) up to 1m distance from tree hedgerows at 1.5 m spacing was 26.18 and 22.84 kg ha-1 day-1, respectively as compared to 32.06 and 30.58 kg ha-1 day-1 in control. Production efficiency was comparatively lower during third year than during second year of hedgerow growth. Root number, length and root growth potential of wheat were affected to greater extent in plants growing nearer to the hedgerows. Higher photosynthesis, transpiration and water use efficiency were recorded in wheat plants growing in association with hedgerows having wider tree spacings, however, closer hedgerow tree spacings as well as closer distance from hedgerows adversely affected physiological parameters in comparison to control (without hedgerows).